VERBALIZATION TOOLS OF THE CONCEPTS OF “SMILE/TABASSUM” IN THE LINGUISTIC LANDSCAPE OF THE WORLD (on the example of english and uzbek languages) (TAMADDUN NURI JURNALI, 2024)
Emotions play a central role in the interaction of people together, and their oral speech differs in languages and cultures. The concepts of “smile” (in English) and “tabassum” (in Uzbek) reflect how emotional states such as happiness, friendship and social harmony are linguistically encoded. This article focuses on the study of the verbalization tools used to express these concepts in the linguistic landscape of English and Uzbek.